Impact of Online Learning on Refractive Error Prevalence in School-Aged Children: A Cross-Sectional Study - Ghosh, Robin (Journal of Educational Research and Policies, 2025)
Background: Uncorrected refractive errors are a major cause of visual impairment worldwide, with a growing number of affected individuals. Children, especially those in the pediatric age group, are particularly vulnerable. The increase in screen time due to online education during the COVID-19 pandemic has raised concerns about its impact on children's vision. This study aims to assess the impact of online classes on refractive errors among school-going children. Methods: A cross-sectional study was conducted among school- going children aged 10-17 years presenting to the OPD with complaints of visual disturbances and related symptoms between January and March 2023. A total of 116 children attending online classes were selected. They completed a questionnaire regarding digital device use, and a complete visual assessment, including refraction by wet retinoscopy, was performed. Data were compared with a similar cohort from January to March 2019. Results: A total of 178 children presented with visual disturbances in 2023, of which 116 participated in the study. In 2019, 122 children presented with visual disturbances, and 116 were selected for comparison. There was a 35% increase in OPD visits due to visual disturbances from 2019 to 2023. Among the 2023 cohort, 33% of children were newly diagnosed with refractive errors, 41% experienced worsening of pre-existing errors, and 27% reported asthenopic symptoms. Myopia was the most prevalent refractive error, with a 16% increase in newly diagnosed cases and a 15% increase in worsening of pre-existing myopia cases. Conclusion: The transition to online education during the COVID-19 pandemic significantly impacted the ocular health of school-going children. Prolonged screen exposure led to increased cases of refractive errors, particularly myopia, as well as associated symptoms like eye strain and headaches. Strategies such as reducing screen time, promoting outdoor activities, and educating parents about digital eye strain are recommended to mitigate these effects.